Design of biomedical passive RFID tag antenna - Slimi, Marwa (2018)
This work is devoted to the study and design of passive RFID tag antenna, this tag can be used in biomedical applications; Essentially for detection of the patient’s condition in a hospital. This study based on the electromagnetic simulation results, the proposed test is given by Computer Simulation Technology Microwave Studio (CST-MWS) based on finite integration technique (FIT) method. We propose a dipole tag antenna in the 2.4-2.48 GHz Industrial Scientific Medical (ISM) band that’s meant to be incorporated in a wristband of a patient. The wristband antenna in free space has a good results in terms of S11 (-33dB), gain (2.73dB), directivity (2.89dBi), bandwidth (5.3%) and efficiency (97%). In order to study the effect of the human body on the performance of the antenna, this wristband will be placed on a phantom arm. Despite the high losses introduced by the human tissue, the antenna shows a good S11 (-17.8dB), gain (1.31dB), directivity (4.06dBi), bandwidth (5.7%) and efficiency (49%).